Hydrology, vegetation, and climate change in the southern Everglades during the Holocene - Winkler, M. G.; Sanford, P. R.; Kaplan, S. W. (Bulletin of American Paleontology, 2001)
Paleoecological study of 18 AMS-dated sediment cores from the southern Everglades provides evidence of a shifting mosaic of biotic communities in the past similar to those on the Everglades landscape today. Our results also indicate initiation of Everglades peatlands at 5900 yr B. P., the importance of fire (from charcoal analysis) as a structuring agent in the tropical Everglades, evidence of past plant communities (Isoetes marshes) not present in the modern landscape, and the introduction of exotic plants (Schinus, Casuarina, etc.) today. Past vegetation changes are documented by pollen and sclereid changes. Past water level changes are documented by plant community changes, diatom species and habitat changes, sponge spicule changes, and by intervals of peat (wet) or marl (dry) deposition in the sediment cores. Marl deposition dominates today at these sites in the southern Everglades, a long-term trend exacerbated by human impacts. The Everglades may become less complex in the near future as introduced plants outcompete native vegetation and decreased water levels result in decreased peat production. A rewatering plan must include both wet and dry seasonal cycles in order to preserve the shifting mosaic nature of the landscape and to maintain the Everglades as a functional habitat for both plants and animals.
id: 125

Environmental changes in the last centure in Little Trout Lake, Inkspot Bay, Great Corn and Little Corn Lakes, Lac du Flambeau Tribal Lands, Wisconsin. Report - Winkler, M. G.; Sanford, P. R. (2000)
id: 128

Holocene climate in the western Great Lakes national parks and lakeshores: Implications for future climate change - Davis, M.; Douglas, C.; Calcote, R.; Cole, K. L.; Winkler, M. G.; Flakne, R. (Conservation Biology, 2000)
We reconstruct Holocene climate history (last 10,000 years) for each of the U.S. National Park Service units in the western Great Lakes region in order to evaluate their sensitivity to global warming. Annual precipitation, annual temperature, and July and January temperatures were reconstructed by comparing fossil pollen in lake sediment with pollen in surface samples, assuming that ancient climates were similar to modern climate near analogous surface samples. In the early Holocene, most of the parks experienced colder winters, warmer summers, and lower precipitation than today. An exception is Voyageurs National Park in northern Minnesota where, by 8000 years ago, January temperatures were higher than today. The combination of high mean annual temperature and lower precipitation at Voyageurs resulted in a dry period between 8000 and 5000 years ago, similar to the Prairie Period in regions to the south and west. A mid-Holocene warm-dry period also occurred at other northern and central parks but was much less strongly developed. In southern parks there was no clear evidence of a mid-Holocene warm-dry period. These differences suggest that global model predictions of a warm, dry climate in the northern Great Plains under doubled atmospheric CO2 may be more applicable to Voyageurs than to the other parks. The contrast in reconstructed temperatures at Voyageurs and Isle Royale indicates that the ameliorating effect of the Great Lakes on temperatures has been in effect throughout the Holocene and presumably will continue in the future, thus reducing the potential for species loss caused by future temperature extremes. Increased numbers of mesic trees at all of the parks in the late Holocene reflect increasing annual precipitation. This trend toward more mesic conditions began 6000 years ago in the south and 4000 years ago in the north and increased sharply in recent millennia at parks located today in lake-effect snow belts. This suggests that lake-effect snowfall is sensitive to continental-scale changes in climate and could be affected by future climate change. Plant and animal species sensitive to changes in the moisture regime could thus be endangered within the Great Lakes parks.
338uvTimes Cited:47Cited References Count:46

Environmental changes in the last centure in Little Trout Lake and Inkspot Bay, Lac du Flambeau Tribal Lands, Wisconsin. Preliminary Results Report - Winkler, M. G.; Sanford, P. R. (Water Resources Division, Lac du Flambeau Tribe, 1999)
id: 1320

Environmental changes since deglaciation in Voyageurs National Park: A summary for park personnel in Holocene Paleoenvironnments in Western Great Lakes Park. Report - Winkler, M. G.; Sanford, P. R. (National Park Service, 1998)
id: 129

Western Great Lakes paleoecology study, global climate change initiative. In Holocene Paleoenvironments in Western Great Lakes Parks. Report - Winkler, M. G.; Sanford, P. R. (National Park Service & USGS Biological Resources Div., Northern Prairie Wildlife Research Center, 1998)
id: 130

Late Quaternary climate, fire, and vegetation dynamics (Book Section) - Winkler, M. G. (Sediment Records of Biomass Burning and Global Change, 1997)
id: 134

Paleocology research in Great Lakes (U.S.A.)National Parks - Winkler, M. G. (Abstracts for American Society of Limnology and Oceanography, 1997)
id: 1300

Paleoecological research at Isle Royale, Apostle Islands, and Voyageurs National Parks. Report - Winkler, M. G.; Sanford, P. R. (1997)
id: 1321

Paleolimnology research at Isle Royale, Apostle Island, and Voyageurs National Parks - Winkler, M. G.; Sanford, P. R. (USGS Biological Resources Division, Global Change Research Program, 1997)
id: 1299

Preliminary paleoecology study of Salt Pond and Nauset Lagoon, Cape Cod National Seashore (Report) - Cole, K.; Winkler, M. G.; Sanford, P. R. (National Park Service, North Atlantic Region, 1997)
id: 131

Western Great Lakes Paleoecology Study. Report - Winkler, M. G.; Sanford, P. R. (National Biological Service Global Climate Change Initiative, 1997)
id: 1322

Western Great Lakes regional paleoenvironmental changes: island and inland contrasts - Winkler, M. G.; Sanford, P. R.; Cole, K. L.; Flakne, R. L. (Ecological Society of America Bulletin, 1997)
id: 1301

Diatom and sediment evidence for late Holocene hydrologic changes, Everglades National Park - Winkler, M. G.; Kaplan, S. (ASLO Meeting, 1996)
id: 1303

One thousand years of change in the Great Lakes Region. A pilot project of the NBS Landscape Use History of North America (LUHNA) publ. electronically on the World Wide Web - Cole, K. L.; Davis, M. B.; Winkler, M. G. (1996)
id: 1323; http://www.nbs.gov/luhna/cole

The paleoecology and pH history of Ike Walton Lake and comparison with the recent history of Zee Lake. Report - Winkler, M. G. (Lac du Flambeau Water Resources Program Contract #1243, 1996)
id: 1325

Paleoecology of the Everglades National Park Paper - Winkler, M. G.; Sanford, P. R.; Kaplan, S. W. (Florida Bay Science Conference, 1996)
id: 1298

Paleoecology of the Everglades National Park. Report - Winkler, M. G.; Sanford, P. R.; Kaplan, S. (National Park Service, Everglades National Park, 1996)
id: 1324

Ryder Pond: A drought-induced natural acidification experiment - Winkler, M. G.; Portnoy, J. (Ecological Society of America (ESA) meeting, 1996)
id: 94

Coastal Massachusetts Pond Development - Edaphic, Climatic, and Sea-Level Impacts since Deglaciation - Winkler, M. G.; Sanford, P. R. (Journal of Paleolimnology, 1995)
Kettle ponds in the Cape Cod National Seashore in southeastern Massachusetts differ in their evolution due to depth of the original ice block, the clay content of outwash in their drainage basins, and their siting in relation to geomorphic changes caused by sea-level rise, barrier beach formation, and saltmarsh development. Stratigraphic records of microfossil, carbon isotope, and sediment changes also document late-glacial and Holocene climatic changes.The ponds are separated into 3 groups, each of which follow different development scenarios. Group I ponds date from the late-glacial. They formed in clay-rich outwash, have perched aquifers and continuous lake sediment deposition. The earliest pollen and macrofossil assemblages in Group I pond sediments suggest tundra and spruce-willow parklands before 12 000 yr B.P., boreal forest between 12 000 and 10 500 yr B.P., bog/heath initiation and expansion during the Younger Dryas between 11 000 and 10 000 yr B.P., northern conifer forest between 10 500 and 9500 yr B.P., and establishment of the Cape oak and pitch pine barrens vegetation after 9500 yr B.P. Sedimentation rate changes suggest lowered freshwater levels between 9000 and 5000 yr B.P. caused by decreased precipitation on the Atlantic Coastal Plain. Lake sediment deposition began in the middle Holocene in Group II ponds which formed in clay-poor outwash. These ponds date from about 6000-5000 yr B.P. In these ponds sediment deposition began as sea level rose and the freshwater lens intersected the dry basins. The basal radiocarbon dates of these ponds and stable carbon isotope analyses of the pond sediments suggest a sea-level curve for Cape Cod Bay. Holocene topographic changes in upland and the landscape surrounding the ponds is reconstructed for this coastal area.Group III ponds in the late Holocene landscape of the Provincelands dunes originated as interdunal bogs about 1000 yr B.P. and became ponds more recently as water-levels increased. Feat formation in the Provincelands reflects climatic changes evident on both sides of the Atlantic region.
Td951Times Cited:1Cited References Count:62

The development of the Gull Pond Chain of Lakes and the Herring River Basin in the Cape Cod National Seashore. Report - Winkler, M. G. (1994)
id: 93

The modern limnology of the interdunal Provincelands Ponds in the Cape Cod National Seashore. Technical Report. Final Report - Winkler, M. G. (National Park Service, North Atlantic Region, 1994)
id: 136

Sensing plant community and climate change by charcoal-carbon isotope analysis - Winkler, M. G. (Ecoscience, 1994)
Mass spectrometric carbon isotope (delta C-13) analyses of charcoal-carbon found in lake sediments provide evidence of paleoclimate and paleovegetation independent of pollen. By chemically separating the microscopic charcoal-carbon, which originates from upland fires, from total carbon in lake, ocean, or ice cores, changes in C-3/C-4 biomass of upland plant communities can be measured, wet or dry climates identified, and the evolution of specific plant assemblages traced. In the North American Midwest, delta C-13 values of lake sediment charcoal-carbon from Lake Mendota, Wisconsin, U. S. A., document two shifts from C-3 (forests) to C-4 (prairie grasses) plants since deglaciation: an abrupt change at about 8.5 ka (8 500 years BP) and a longer duration change between 6 and 3 ka. A pine-savannah is interpreted for the earlier date while oak-savannah dominated the landscape between 6 and 3 ka. C-4 biomass, which was almost non-existent in the region before 8.5 ka, increased to more than 50% between 6 and 3 ka. Spruce-tundra parkland evident in the Midwest before about 12 ka contained no C-4 grasses and was probably similar in composition to modern North American tundra-parkland which has no C-4 biomass. The climate inferred from the delta C-13 data compares well with climate inferred from pollen and sediment data from the same core and supports climate model simulations of decreased effective moisture during the middle Holocene in the North American Midwest. The delta C-13 results also suggest future landscape changes should greenhouse-gas warming occurs. Savannah, with increased C-4 biomass, could again become prevalent in the North American Midwest.
V19xpTimes Cited:10 Cited References Count:44
Keywords: c-3/c-4 plants; midwestern u. s.; paleoclimatology; paleovegetation; sediment charcoal; stable carbon isotopes